Current knowledge and future perspectives of barrier membranes: A biomaterials perspective - Carole CHAKAR; Sara KHALIL; Nadim MOKBEL; Abdel Rahman KASSIR (International Arab Journal of Dentistry (IAJD), 2020)
Periodontal regenerations and bone augmentations are common procedures practiced on a daily basis worldwide. This had led to the introduction of a wide number of barrier membranes, all aiming at regenerating a sufficient amount of bone while being safe, cost effective and easy to handle. Membranes have different characteristics that may influence their clinical properties and the result obtained. The article aims at presenting an overview of the different barrier membranes commonly used in the oral surgery field, while shedding light on the new advances in the third generation membranes.